Jazzband Groups and First Popular Music Studies in Sivas - Erdoğan, Göktürk (Fırat University, 2023)
Sivas, which constitutes one of the strongest veins of thousands of years of musical heritage in Anatolia, has been one of the cities that enrich our music culture not only with folk music but also with popular music works. In this study, beyond traditional folk music works, the first popular music works that started in Sivas especially after the second half of the twentieth century are discussed. In this sense, it was tried to examine what kind of works were carried out in Sivas in the name of popular music, especially in the 1960 and later period, with the oral history method, and it was aimed to bring to light a musical memory that is almost hidden today. Interviews with the living representatives of the period and document analysis revealed that there was a very active popular music scene in Sivas between 1960 and 1985, and that modern Western instruments such as double bass, saxophone, drums, bass guitar and accordion shaped the musical and cultural life in Sivas. These popular music formations, which were characterized as "jazzband" at the time and shaped by individual efforts, added richness to the existing music culture of the city, but it is understood that they have not been in demand since the mid-1980s.

Anadolu’da binlerce yıllık müzikal mirasın en güçlü damarlarından birini oluşturan Sivas sadece halk müziği ile değil aynı zamanda popüler müzik çalışmalarıyla da müzik kültürümüzü zenginleştiren şehirlerden biri olmuştur. Bu çalışmada geleneksel halk müziği çalışmalarının ötesinde Sivas’ta özellikle XX. yüzyılın ikinci yarısından sonra başlayan ilk popüler müzik çalışmaları ele alınmıştır. Bu anlamda Sivas’ta özellikle 1960 ve sonrası dönemde popüler müzik adına ne gibi çalışmalar yapıldığı sözlü tarih yöntemiyle incelenmeye çalışılmış ve bugün adeta saklı kalmış bir müzikal hafızanın gün yüzüne çıkartılması amaçlanmıştır. Dönemin yaşayan temsilcileriyle yapılan görüşmeler ve doküman incelemeleri sonucu ortaya çıkan bilgiler, Sivas’ta 1960 ve 1985 yılları arası çok hareketli bir popüler müzik ortamının olduğu, kontrbas, saksafon, bateri, bas gitar ve akordeon gibi modern Batı sazlarının Sivas’ta müzikal ve kültürel hayatı şekillendirdiği anlaşılmaktadır. O dönemki adıyla “cazband” olarak nitelendirilen ve bireysel çabalarla şekillenen bu popüler müzik oluşumları, şehrin var olan müzik kültürüne zenginlik kattığı ancak 1980’li yılların ortalarından itibaren rağbet görmediği anlaşılmaktadır.
SİVAS’TA CAZBAND GRUPLARI VE İLK POPÜLER MÜZİK ÇALIŞMALARI